Teacher Candidates’ Efficacy Beliefs in Mathematics: Play-Generated Curriculum Instruction - Incikabi, Lutfi (Modestum Publishing Ltd, 2013)
The aim of this study was to present changes, if any exist, in early childhood teacher candidates’ mathematics teaching efficacy beliefs (MTEB) after the implementation of a play-generated curriculum approach. This experimental one-group pretest-posttest design utilized qualitative data through an open-ended questionnaire conducted at the end of the instruction. Thirty-seven second-year college students from the Early Childhood Education department at Mersin University participated in the study. Among the instruments used during the study were a questionnaire for the participants’ demographics, a Turkish version of MTEBI for teacher candidates, an open-ended questionnaire focusing on the difficulties confronted by teacher candidates during the preparation and implementation of a lesson plan utilizing the play-generated curriculum approach and lesson observation form. The results indicate that early childhood education teacher candidates’ mathematics teaching efficacy beliefs when combined with their personal mathematics teaching and outcome expectancy beliefs possessed a positive and statistically significant change after they prepared play-based instruction.
Keywords: 4. Education